2015
DOI: 10.1186/s12906-015-0576-9
|View full text |Cite
|
Sign up to set email alerts
|

Can red yeast rice and olive extract improve lipid profile and cardiovascular risk in metabolic syndrome?: a double blind, placebo controlled randomized trial

Abstract: Background: Metabolic syndrome (MetS) comprises a spectrum of clinical phenotypes in which dyslipidemia, dysglycemia and hypertension are clustered and where all share a high level of oxidative stress and an increased risk of cardiovascular disease. This study examines the effect of a nutritional supplement combining red yeast rice and olive fruit extract on the lipid profile and on oxidative stress in a population of patients with MetS. Methods: In a double blind placebo controlled randomized trial, 50 person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 43 publications
5
31
1
2
Order By: Relevance
“…Quite remarkably, the ratio of total over HDL cholesterol was clearly reduced since HDL-cholesterol was increased, together with the rather strong decrease of LDL cholesterol, confirming the results of recent controlled trials [21,22].…”
Section: Discussionsupporting
confidence: 84%
“…Quite remarkably, the ratio of total over HDL cholesterol was clearly reduced since HDL-cholesterol was increased, together with the rather strong decrease of LDL cholesterol, confirming the results of recent controlled trials [21,22].…”
Section: Discussionsupporting
confidence: 84%
“…These results were not surprising to us on the basis of the anti-inflammatory and antioxidant activity of 5-hydroxytyrosol that has already been described independently [23,28,29]. Also in previous clinical assays, there was no evidence of significant toxicity [30]. Although we have not included nonoxynol-9 as a positive control in our in-vivo toxicity study, other authors have done it previously with similar methodology to assess spermicide activity.…”
Section: Resultssupporting
confidence: 71%
“…Verhoeven et al [3] conducted a double-blind, placebo-controlled, randomized trial in 50 subjects with metabolic syndrome, as defined by ATP III (Adult Treatment Panel III) criteria. Patients received capsules containing 10.82 mg of monacolins and 9.32 mg of hydroxytyrosol or placebo for 8 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidized LDL decreased by 20% in the intervention group and increased by 5% in the control group ( P  < 0.001). The investigators concluded that the combination of active products (which included hydroxytyrosol as well as the statin [HMG-CoA reductase inhibitor] monacolin) in this study may be an alternative therapeutic approach in people who do not need, cannot, or do not want to be treated with chemical statins [3]. …”
Section: Introductionmentioning
confidence: 99%